Sistem Informasi Pariwisata di Kecamatan Gunungpati Berbasis Web Menggunakan Framework Codeigniter dan Bootstrap - Dewi, Septiyana; Harlanu, Muhammad; Ananta, Henry (Jurusan Teknik Elektro Universitas Negeri Semarang, 2016)
Tourism Information System was designed as a promotional media that provides information on tourist attractions in the district Gunungpati to the general public. This information system is developed using CodeIgniter and Bootstrap framework and the waterfall model. Testing of information systems covering the aspects of functionality, usability, and portability is based on ISO 9126. The implementation results obtained from the questionnaire responses from user and admin. The results showed using CodeIgniter and Bootstrap framework can be created the tourism information system in district Gunungpati. The test results on the aspect of functionality stated very decent with 100% functionality goes well. Results of testing the usability aspect stated very decent system with a result of 90%. In the aspect of portability, show very decent results ie 99% of the system can be run on different web browsers. Admin system implementation results obtained from questionnaires filled out by employees of the District Gunungpati expressed very well with the results of 94% admin easily manage the data on the system. While the results of the implementation of the system obtained from questionnaires filled out by 31 respondents who expressed very well with the results 86% of users can easily use the system.